2017
DOI: 10.5334/irsp.82
|View full text |Cite|
|
Sign up to set email alerts
|

Why Psychologists Should by Default Use Welch’s t-test Instead of Student’s t-test

Abstract: When comparing two independent groups, psychology researchers commonly use Student's t-tests. Assumptions of normality and homogeneity of variance underlie this test. More often than not, when these conditions are not met, Student's t-test can be severely biased and lead to invalid statistical inferences. Moreover, we argue that the assumption of equal variances will seldom hold in psychological research, and choosing between Student's t-test and Welch's t-test based on the outcomes of a test of the equality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
423
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 717 publications
(436 citation statements)
references
References 41 publications
2
423
0
11
Order By: Relevance
“…According to Satterthwaite (1946), issues with homogeneity of variance can be avoided by utilizing a linear function of mean squares to estimate variance. Delacre, Lakens, and Leys (2017) suggested that the Welch's t-test for unequal variances is appropriate under these circumstances and will return results that are less likely to result in a Type 1 error of rejecting a null hypothesis when it is true if the study data assumption of homogeneity is not met.…”
Section: Resultsmentioning
confidence: 99%
“…According to Satterthwaite (1946), issues with homogeneity of variance can be avoided by utilizing a linear function of mean squares to estimate variance. Delacre, Lakens, and Leys (2017) suggested that the Welch's t-test for unequal variances is appropriate under these circumstances and will return results that are less likely to result in a Type 1 error of rejecting a null hypothesis when it is true if the study data assumption of homogeneity is not met.…”
Section: Resultsmentioning
confidence: 99%
“…Admittedly, the extent of this problem differs depending on the planned test. For instance, the Welch t test, for unequal variances, barely has lower power than the standard Student t test (Delacre, Lakens, & Leys, 2017).…”
Section: Strategy 2: Selecting a Robust Primary Analysis Strategymentioning
confidence: 99%
“…(1) perceptions about alcohol usage in their local environment, Statistical tests were used to estimate the significance of any observed differences. The Welch t-test was applied when comparing the responses of intervention groups and control groups (Delacre et al, 2017). When the differences between all participant schools from A to E were examined, Welchís ANOVA was used as the statistical tests and Games-Howell as a post-hoc test (Field, 2013, 442ñ459).…”
Section: Data Sources and Data Analysismentioning
confidence: 99%
“…When the differences between pre-and post-test responses in a single group were examined, the paired sample t-test was applied because it tolerates skewness and nonnormality in the distribution (Delacre et al, 2017).…”
Section: Data Sources and Data Analysismentioning
confidence: 99%